Response of elephant grass to grazing under an organic production system - Vinicius Felipe Bratz; Clair Jorge Olivo; Julia Aires Fernandes; Daiane Cristine Seibt; Vinicius Alessio (Revista Ciência Agronômica)
ABSTRACT The aim of this research was to evaluate elephant grass under an organic and a conventional system. Under the organic system, species with complementary growth periods were combined; elephant grass was planted in rows 3.0 m apart and ryegrass was sown between the rows of elephant grass during the winter period, with spontaneous species being allowed to develop during the summer period. For the conventional production, two types of pasture were studied: one using the same strategy as for the organic production, and the other with a monocrop of elephant grass. Under the conventional and organic systems, 120 kg of N ha-1 were applied as chemical and organic fertiliser (cattle manure and pig slurry) respectively. Holstein cows were used in the evaluation. The experimental design was completely randomised, with three treatments (forage systems), three replications (paddocks) and measurements repeated over time (season). During the experimental period (370 days), nine grazing cycles were carried out under the organic and conventional systems (elephant grass in association with other forages) and eight grazing cycles under the conventional system (a monocrop of elephant grass). Forage production was 31.6, 32.8 and 24.2 t ha-1, and the stocking rate was 3.4, 2.1 and 4.6 AU ha-1 day-1 under the respective systems. Better results for forage production and distribution were found under the organic and conventional systems including a mixture of forages. The best results for leaf to stem ratio in the elephant grass and for stocking rate were seen under the monocrop system.